Disability in the time of pandemic - Carey, Allison C.; Green, Sara E.; Mauldin, Laura (Research in social science and disability, 2023)
COVID-19 has once again illuminated the ways in which health risks and negative health outcomes are tied to economic and social inequalities. Disabled people rank among those most disadvantaged in terms of education, income, and social inclusion and this exacerbated their risk of negative pandemic-related outcomes. From the start, it was clear that disabled people would be disproportionately affected by the pandemic and this solidified as the pandemic unfolded. Disability in the Time of Pandemic is a timely exploration of emerging research into the implications of the COVID-19 pandemic for people with disabilities in their varied communities and across their complex identities. Using the insights, perspectives, and methods of a variety of disciplines including Anthropology, Disability Studies, Education, Physical and Rehabilitation Therapies, Public Health, Psychology, Sociology, and Women's and Gender Studies, authors explore the initial and ongoing effects of the global pandemic on people with disabilities in Canada, India, Poland, and the United States. The Research in Social Science and Disability series is essential reading for researchers and students across the social sciences interested in disability, social movements, activism, and identity.